Relations of coping strategies and cognitive emotion regulation to Chinese children’s academic achievement goals and academic performance - Chen-Bouck, Li; Patterson, Meagan M.; Peng, Anqi (Frontiers in Psychology, 2024)
Social-emotional skills (e.g., emotion regulation) influence a variety of academic outcomes among children. This study examined the relations of coping strategies and cognitive emotion regulation (CER) to academic achievement goals and academic performance among Chinese children (N = 401, age M = 10.52 years). Full Structural Equation Modeling (SEM) analysis showed that children's use of active coping strategies was positively associated with their endorsement of performance approach and mastery avoidance goals. Avoidant and supportseeking coping strategies were not associated with any outcome variables. Maladaptive CER was positively associated with performance approach, performance avoidance, and mastery avoidance goals and negatively associated with academic performance; adaptive CER was positively associated with mastery approach goals but not associated with other outcome variables. The current study provided some preliminary evidence to indicate that active coping strategies, maladaptive CER, and adaptive CER were associated with academic achievement goals and academic performance among Chinese children. Although maladaptive CER was not used as often as adaptive CER by Chinese children, the more they used maladaptive CER, the more likely they were to have academic achievement goals that focused on things other than learning itself, whereas the more Chinese children used adaptive CER, the more likely they were to set an achievement goal to master the knowledge. Therefore, in teaching practices or intervention planning, decreasing maladaptive CER strategies may be as important as cultivating adaptive CER strategies to facilitate academic success among Chinese children.